IINVESTIGATION OF THE CATALYTIC AND ISOMERIZATION ACTIVITY OF MULTI-COMPONENT SKELETAL NICKEL CATALYSTS IN THE HYDROGENATION OF HEXENE-1 - Zh. K. Kairbekov; S. M. Suimbayeva; I. M. Jeldybayeva; E. T. Yermoldina (Academic Scientific Journal of Chemistry, 2021)
In this work, the effect of the amount of catalyst, modifying additives, and the phase composition of the alloys on the catalytic and isomerizing activity of skeletal in the hydrogenation reaction of hexane-1 is investigated. It has been shown that for all studied catalysts, the yield of products in the processes of migration and isomerization depends very strongly on the weighed portion of the catalyst introduced into the reaction medium. So, for example, the yield of hexane-2 with an increase in the catalyst weight increases linearly to 0.5g of nickel, while at the initial stage of the reaction the yield of hexane-2 reaches 62%. With a further increase in the catalyst weight (up to 1 g of Ni), the yield of hexane-2 decreases. The results of chromatographic analysis indicate a high activity of modified skeletal nickel catalysts in the reaction of migration of -C = C- bonds during hydrogenation of hexene-1. Modification of Fe, Pd, Sn and Ag increases the migration coefficient (Kmigr) from 0.66 to 0.70-0.77, while additions of Ti, Mo, Ti-Mo and Zr practically do not change it. The activity of the catalyst increases with the introduction of the metals Cu, Zn, Pb, Ti-Mo, Mo, Bi, Ag, and Mo-Cu (W=120-290 cm3 /minꞏg Ni) into the initial alloy, while the addition of Fe, Pd and Mn (W=56-80 cm3 /minꞏg Ni), while the influence of the components Ti, Zr and Sn is insignificant (W=115-117 cm3 /minꞏg Ni)